AB0771 Tocilizumab in patients with recent onset polymyalgia rheumatica (PMR) and contraindications to steroid use. (23rd January 2014) - Boiardi, L.; Macchioni, P.; Catanoso, M.; Salvarani, C.
Abstract : Background: Corticosteroids (CS) are the drug of choice in treating polymyalgia rheumatica (PMR). However CS-related adverse events are frequently observed during treatment course. A previous report showed that tocilizumab (TCZ) is able to control signs and symptoms of PMR patients who are resistant to CS therapy (1). Objectives: To evaluate the safety and efficacy of TCZ in the treatment of recent onset (PMR) in patient with contraindications to the use of CS. Methods: Two patients entered the study. According to treatment protocol TCZ was administered at a dose of 8 mg/kg ev every four weeks for 6 months without use of CS. Pts were evaluated at baseline and then every month for the following measures of disease activity: pain (10 cm VAS), patient and physician global assessment, HAQ, duration of morning stiffness, ESR and CRP. Disease activity score (DAS) according to Leeb were calculated at every visit (2). Serum IL-6 and serum IL-6 receptor was evaluated at each visit. Patient were permitted to initiate CS in the case of absent or incomplete response to TCZ. The presence of adverse events were considered at every visit. Results: Table 1 shows demographic characteristics of the two female patients and the main outcome measures at 6 months as percentage variation (Δ) 6 month study visit vs baseline. The first patient had disease recurrence 6 months after the end of the TCZ treatment course. The second one was treated with CS (prednisone 4 mg/day) after two infusion of TCZ because of a partial response (Leeb's DAS 37.01). No adverse event was observed during TCZ therapy. TCZ treatment induced a marked increase of serum IL-6 and serum IL-6 receptor concentration. Conclusions: In patients with recent onset PMR, TCZ treatment seems to be able to partially control PMR symptoms without use of CS. In our two patients TCZ was well tolerated. As observed in other diseases TCZ treatment induced a marked increase of serum IL-6 and serum IL-6 receptor concentration. References: Hagihara K, Kawase I, Tanaka T, Kishimoto T. Tocilizumab ameliorates clinical symptoms in polymyalgia rheumatica. J Rheumatol. 2010;37:1075-6. Leeb BF, Bird HA. A disease activity score for polymyalgia rheumatica. Ann Rheum Dis. 2004;63:1279-83. Disclosure of Interest: None Declared